Feng Xiaogang’s New Year celebration films and contemporary Chinese commercial cinema: industry, regulatory authority and pop culture - Ai, Qi (2020)
Since the 1993 market-oriented reform, the Chinese government has strengthened its role in the domestic film industry’s commercialisation. Feng Xiaogang’s New Year Celebration Films (hesui pian, NYCFs), by virtue of their impressive box-office performance, are a valuable indicator of how commercial imperatives work in tandem with ideological prescriptions and state censorship to shape contemporary Chinese commercial filmmaking. This thesis selects, as case studies, Feng’s eight NYCFs of modern urban life across the period from the late 1990s, when he began making films in this mode with governmental support, to the 2000s, when his NYCFs address genre shift in the context of China’s entry to the WTO: Party A, Party B (Jiafang yifang, 1997), Be There or Be Square (Bujian busan, 1998), Sorry Baby (Meiwan meiliao, 1999), Sigh (Yisheng tanxi, 2000), Big Shot’s Funeral (Dawan, 2001), Cell Phone (Shouji, 2003), A World Without Thieves (Tianxia wuzei, 2004) and If You Are The One (Feicheng wurao, 2008). It investigates how the political economy of the Chinese film industry — comprising three interactive aspects in this context, industry commercialisation, government regulation and popular culture — produced Feng’s NYCFs as a popular commercial genre. To facilitate this investigation, this thesis merges textual, industrial and cultural-policy analysis, combining film texts with attention to the government’s cultural and industrial policies, film regulations and censoring rules, the Party’s political philosophies and relevant campaigns in the film sphere, the trend in popular culture of humour from the late 1980s to the 2000s, and interview materials involving Feng and his close collaborators. It argues that Feng’s filmmaking, along with the three categories’ mutual construction, appropriates popular humorous expression to integrate political promotion and commercial return. This market-approved integration, in turn, promotes the film industry’s state-led commercialisation, with regulatory authorities using economic and administrative means to infuse state propaganda into domestic filmmaking and thus, consolidate the Party’s cultural hegemony. This thesis contributes to a nuanced understanding of the relationship between state, film industry, and filmmakers. Taking a political economy perspective, it uses Feng’s NYCF production as a lens through which to illuminate Chinese cinema’s production culture, in the context of state-led commercialisation. In addition, the thesis offers a new model that acknowledges the intersection of popular culture and ideology in constructing cultural hegemony, and further, highlights the role of the popular culture of humour in coordinating state propaganda and social critique in contemporary Chinese commercial cinema.